The hormone regulatory mechanism underlying parthenocarpic fruit formation in tomato - Guan, Hongling; Yang, Xiaolong; Lin, Yuxiang; Xie, Baoxing; Zhang, Xinyue; Ma, Chongjian; Xia, Rui; Chen, Riyuan; Hao, Yanwei (Frontiers in Plant Science, 2024)
Parthenocarpic fruits, known for their superior taste and reliable yields in adverse conditions, develop without the need for fertilization or pollination. Exploring the physiological and molecular mechanisms behind parthenocarpic fruit development holds both theoretical and practical significance, making it a crucial area of study. This review examines how plant hormones and MADS-box transcription factors control parthenocarpic fruit formation. It delves into various aspects of plant hormones-including auxin, gibberellic acid, cytokinins, ethylene, and abscisic acid-ranging from external application to biosynthesis, metabolism, signaling pathways, and their interplay in influencing parthenocarpic fruit development. The review also explores the involvement of MADS family gene functions in these processes. Lastly, we highlight existing knowledge gaps and propose directions for future research on parthenocarpy.